PERMAINAN WHEEL SPINNING UNTUK PEMBELAJARAN MENULIS TEKS DESKRIPTIF DI KELAS VII SMP - Yusniarsi Primasari; Hesty Puspita Sari; Nita Sutanti; Syifa Mareta (Program Studi PGSD Universitas Flores, 2023)
Students' writing mastery in descriptive texts tends to decline. The limitations of effective writing learning media are one of the causes of students' decreased interest in writing. This research was aimed at understanding the wheel spinning game effect to facilite on writing descriptive text for seventh grade students and to understand the feasibility of these facilities. Using research was Research and Development Design with Sugiyono's adaptation model, which includes; Data Collection and Finding Potential, Problem and Solution, Design and Development, Experts Validation and Revision, Trial, Evaluation by Experts and Revision, and Final Product. Researchers used class VII B students at UPT SMPN 2 Talun as research objects totaling 30 students. The research obtained quantitative data from the result of questionnaire and tests while the qualitative data was obtained from interview. The result of the research development questionnaire in the form of games showed that 79.90% of students agreed with the wheel spinning game media as descriptive text learning. The results of product showed that the wheel spinning for writing of descriptive text was valid, the average material experts was 85% and the average media experts was 83.3%. Test and try to show that the game is effective. The pre-test result was 57.2 and the post-testresult increase to 80.76. The value of t-test with t-count -16.053<t-table 2.045 with a significant value of 0.05. The product was valid and can be used as a facility in the teaching and learning process. The result of student response was 85.20%, the score is very good. Wheel spinning game improves students' writing skills and motivate them to learn. The result of the research above indicates that the wheel spinning game is valid to be used as a tool of learning descriptive writing for class VII students. The next researchers may use this game for the other level of students.